A thief in the village : And other stories - Berry, James (London : Puffin, 1987)
A collection of nine short stories about life in contemporary Jamaica, on such subjects as a young boy's desire to buy shoes for the cricet team and a girl's adventures on a coconut plantation.
Keywords: Short stories